The big three perfectionism scales: A psychometric characterization of a Chinese music student population - Qiujian Xu; Xiaoyu Wang; Mingyi Yang; Bo Wang; Dan Yang; Meihui Li; Shilin Liu; Xiubo Ren; Yintong Liu; Siqi Liu; Minghe Song; Xiaoxuan Bao (PLoS ONE, 2025)
Background Perfectionism as a multidimensional personality trait, is closely related to many important factors affecting mental, emotional, and daily life, and thus has received extensive attention from researchers around the world. The Big Three Perfectionism Scale (BTPS) is a widely recognized tool in global research, providing a comprehensive framework for assessing perfectionism through three higher-order factors and ten dimensions. Objectives This study aims to translate and validate the BTPS in the context of music student population in mainland China, assessing its cross-cultural reliability and psychometric properties to ensure its applicability within this specific population. Methods This study evaluated the factor structure, convergent validity, predictive validity, and overall validity of the Chinese version of the BTPS. The methodology involved translating the BTPS into Chinese and conducting cross-cultural validation through experiments with a substantial sample of musical expertise from Chinese mainland (n ≥  442). Results The results aimed to support the hypothesis that the three-factor structural model of the BTPS demonstrates invariance within this population. Preliminary experimental results indicated that the Chinese version of the BTPS has good validity in the musical expertise population in Chinese mainland (Cronbach’s alpha coefficients of 0.86, 0.95 and 0.94 for the three dimensions, respectively), and the significance of the data (KMO >  0.6, p <  0.05) suggests that it can be further analyzed by exploratory factor analysis (EFA) and validation factor analysis (CFA). Conclusions Our preliminary results show the feasibility of cross-cultural research on the findings of psychometric instruments from other countries, and the authors’ pioneering work is also of practical significance in enriching the psychometric instruments on perfectionism in China, which will provide a valid basis for a series of future studies on perfectionism related to music psychology.